Analisis prioritas faktor kendaraan, manusia, dan jalan terhadap kecelakaan lalu lintas di koridor inspeksi Kalimalang, Bekasi - Nur Wulan Sari; Adenanthera Lesmana; Roesjanto Roesjanto (Indonesian Maritime Researchers and Lecturers, 2025)
The rapid development and population growth in Bekasi Regency, Indonesia, have resulted in increasing traffic density and a corresponding rise in road traffic accidents (RTA), particularly along the critical 28 km Kalimalang Inspection Highway, locally known as